Dimensions of Electronic Fraud and Governance of Trust in Nigeria’s Cashless Ecosystem (2020)
A negative outcome of the nascent cashless policy in Nigeria has been persistent electronic banking fraud (e-fraud). Fraud occurrence in any financial space indicates insecurity and loopholes being exploited by fraudsters. This underscores the importance of trust governance in electronic banking and its centrality in a transiting cashless economy like Nigeria. Against this background, we investigated e-banking fraud and the role trust governance plays in both the adoption and refusal to migrate and use electronic banking in Nigeria. Using qualitative methods (in-depth and key informant interviews) of data collection, 30 participants were purposively selected and, in some instances, reached through the snowball and referral methods. Findings showed internal, external, and collaborative dimensions of e-fraud. Experiences of fraud reportedly affected adoption and migration of bank customers to e-banking platforms. Although weak governance mechanism was reported, banks nonetheless are embracing security mechanisms such as sending SCAM alert messages to customers, while shaming and sack of compromised staff were employed as within-bank measures to secure the confidence of customers in the evolving financial ecosystem.